The electronic structure of transparent conducting oxides - Godinho, Kate Gitanjali (Trinity College (Dublin, Ireland). School of Chemistry, 2011)
Transparent conducting oxides (TCOs) are a unique class of materials which combine the normally mutually exclusive properties of transparency and conduction. Although their discovery dates back over a century and despite their increasing commercial use since the first applications 70 years ago, the exact mechanism of conduction in TCOs is still not fully understood. Conduction in TCOs occurs due to the presence of defects. These can be either intrinsic defects such as oxygen vacancies, or extrinsic dopants which are deliberately introduced into the material.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin.